2013
DOI: 10.1371/journal.pone.0066151
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Reveals Distinct Patterns of Retinal Damage in Neuromyelitis Optica and Multiple Sclerosis

Abstract: BackgroundNeuromyelitis optica (NMO) and relapsing-remitting multiple sclerosis (RRMS) are difficult to differentiate solely on clinical grounds. Optical coherence tomography (OCT) studies investigating retinal changes in both diseases focused primarily on the retinal nerve fiber layer (RNFL) while rare data are available on deeper intra-retinal layers.ObjectiveTo detect different patterns of intra-retinal layer alterations in patients with NMO spectrum disorders (NMOSD) and RRMS with focus on the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
136
2
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 165 publications
(171 citation statements)
references
References 70 publications
(60 reference statements)
17
136
2
12
Order By: Relevance
“…Previous studies have shown that inner macular segmented layers suffered more severe damage in NMO or NMOSD than MS-ON in general, but for each macular segmented layer, there are controversial studies 4 10 16 17 33. Schneider's10 study showed that the average thickness in the mRNFL, RGCL and IPL was lower in NMOSD than MS-ON but was not significantly different in the INL when controlling for MME influences.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that inner macular segmented layers suffered more severe damage in NMO or NMOSD than MS-ON in general, but for each macular segmented layer, there are controversial studies 4 10 16 17 33. Schneider's10 study showed that the average thickness in the mRNFL, RGCL and IPL was lower in NMOSD than MS-ON but was not significantly different in the INL when controlling for MME influences.…”
Section: Discussionmentioning
confidence: 98%
“…OCT studies showed that ON in NMO causes more severe neuronal damage and greater thinning of the retinal nerve fibre layer (RNFL) than ON in MS 34–36. Interestingly RNFL thinning in MS showed clear temporal preponderance, while in NMO it was more widespread 34 37…”
Section: Clinical Phenotypesmentioning
confidence: 99%
“…Although the presence of MMO is related to disability in MS, it is important to note that it is not specific for MS, as MMO is also observed in other diseases [79][80][81][82]. Notably, there have been three recent reports demonstrating MMO in up to 25% of patients with neuromyelitis optica (NMO) [83][84][85]. Therefore, from a clinical practice point of view it may be advised to test for serum anti-AQP4 autoantibodies in those cases with severe ON and MMO, because if positive this will have significant patient management implications.…”
Section: Microcystic Macular Edema In Msmentioning
confidence: 99%